The Effect of Plant Density on the Yield of Sunflower Hybrid’s in 2001-2002 - Szabó, András; Pepó, Péter; Zsombik, László (Acta Agraria Debreceniensis, 2003)
Nowadays, for increasing efficiency of sunflower production treating hybrid-specific technologies was required. Increasing of hybrid choice gave reasons for trials in respects of critical factors, as well as in case of genotype-enviroment interactions. The effect of changing plant density show up as determinant factor which affects on yield as well as on plant hygienic conditions. Trials were established on calcareous chernozem soil (Hajdú-Bihar county), in 2001-2002. The field trials were randomized, in four repetition on small parcels. The plant density trials were established in 35.000-75.000 plant/hectar interval using a scale of 10.000 plant/hectar. 10 hybrids were used in both year.In 2001, 55.000 plant/hectar density was the optimal, in case of most of the hybrids. The yield of tested hybrids did not show significant difference. Yield decreasing effect of using less than optimal density was more significant than in case of using optimal plant density. In 2002, the optimal density was in 45.000-65.000 plant/hectar interval, there was no possibility to find narrower optimum.Presence of Diaporthe helianthi and the damage caused by the pathogen was significant in 1997-1999, whereas in 2001-2002 the large-scale appearance of the pathogen did not occur. In 2001, the affect of high plant density on disease caused by Diaporthe helianthi showed just tendency-like appearance, in 2002, the infection showed up just in the end of the vegetation period, without significant damage. In spite of the low infection level, the difference between the infection of the diverse plant density treatment was significant. Increasing plant density made increase the frequency of the Diaporthe helianthi infection. The rate of the flower diseases was around 3-16% in 2001, the highest infection level emerged in 65.000-75.000 plant/hectar density, whereas in 2002, the rate of infection level was less than 10%. The increasing plant density helped the development of flower diseases.